Preferensi Konsumen Terhadap Produk Fellow Coffee Manado Dan Fellow Coffee Bitung - Mewanglo, Geraldo Putra; Rumagit, Grace Adonia Josefina; Pangemanan, Lyndon R.J. (AGRI-SOSIOEKONOMI, 2024)
This research aims to determine the characteristics and preferences of Fellow Coffee Manado and Fellow Coffee Bitung consumers with 4 attributes, namely price, variants, facilities and service. The research was carried out from June to August 2023. The data collection method used was primary and secondary data. The data collection method used was primary and secondary data. Respondents in this study consisted of 84 samples taken totaling 42 respondents for each location. The sampling technique used was purposive sampling. Data measured using a Likert scale were analyzed using conjoint analysis. In the data processing process, using the SPSS version 27 program as a tool, the data is presented in table format and explained descriptively. The research results show that the order of attributes that have the highest utility for Fellow Coffee Manado is the price attribute of IDR 20.000-IDR 25.000 and the second utility is IDR 25.000-IDR 30.000. Attributes of fellow iced milk coffee variants and the second utility of Cafe Latte. The facility attributes free wifi and utility of both table and chair layouts. The service attributes are fast and the second utility is friendly. Meanwhile, the attribute that has the highest utility for Fellow Coffee Bitung is the price attribute of IDR 20.000-IDR 25.000 and the second utility is IDR 25.000-IDR 30.000. Attributes of the fellow's iced coffee milk variant and the second utility of salted caramel macchiatto. The facility attribute is the availability of electrical plugs and utilities, both the layout of tables and chairs. Friendly service attributes and fast second utility.